2018
DOI: 10.1002/ajb2.1051
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of key metabolic genes during transitions to C4 and CAM photosynthesis

Abstract: Our analyses reveal a new suite of amino acid residues putatively important for C and CAM function. We discuss both the advantages and challenges of using targeted enrichment sequence data for exploratory studies of molecular evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 72 publications
3
22
0
Order By: Relevance
“…C 4 photosynthesis especially has been well studied, perhaps due to the importance of C 4 grasses in agriculture, and we now understand a considerable amount about the evolutionary trajectory of the C 4 syndrome. The same cannot yet be said of CAM, although this is beginning to change (Silvera et al ., ; Horn et al ., ; Bone et al ., ; Heyduk et al ., ; Goolsby et al ., ; Males, ; Hancock et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…C 4 photosynthesis especially has been well studied, perhaps due to the importance of C 4 grasses in agriculture, and we now understand a considerable amount about the evolutionary trajectory of the C 4 syndrome. The same cannot yet be said of CAM, although this is beginning to change (Silvera et al ., ; Horn et al ., ; Bone et al ., ; Heyduk et al ., ; Goolsby et al ., ; Males, ; Hancock et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, convergent evolution in several key amino acid residues of PEPC has been suggested to be associated with the origin of both C 4 and CAM (Christin et al 2007; Christin et al 2014; Goolsby et al 2018). A recent study has also confirmed the occurrence of multiple rounds of duplication within the major PEPC paralog (PEPC1E1) in the ancestral Portulacineae (Christin et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the CGS , HMT and MMT genes have been duplicated and diverged during evolution. In addition, previous research has also proposed that the evolution and divergence of metabolic pathways may be disclosed by comparing the sequence and the structure of genes of the same and different routes from organisms ( Fondi et al, 2007 ; Goolsby et al, 2018 ).Therefore, combining the evolutionary and expressional pattern of CGS , HMT and MMT genes, we proposed the evolutionary and functional models of Met biosynthetic pathway in plant lineages ( Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%